PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP KINERJA KARYAWAN DENGAN BUDAYA ORGANISASI DAN PUBLIC SERVICE MOTIVATION SEBAGAI VARIABEL MEDIASI PADA RUMAH SAKIT UMUM DAERAH KOTABUMI LAMPUNG UTARA - Deswan, Deswan; Jimad, Habibullah; Hayati, Keumala (JURNAL ILMIAH EDUNOMIKA, 2024)
Transformational leadership is a leadership style that inspires followers to set aside personal interests for the good of the organization. If leaders are able to apply transformational leadership styles, employee performance will improve. Transformational leadership is the leadership style at the Kotabumi Regional General Hospital in North Lampung, where leaders encourage rational thinking, challenge the status quo, and ultimately foster creativity and innovation. This study aims to determine and analyze the influence of transformational leadership on employee performance with organizational culture and public service motivation as mediating variables. This research was conducted at the Kotabumi Regional General Hospital in North Lampung with a sample of 270 employees.Â  This research uses the Structural Equation Modeling (SEM) technique, through the AMOS program. (Analysis of Moment Structure). The research findings indicate that transformational leadership has a significant impact on the performance of employees at RSUD Kotabumi Lampung Utara, transformational leadership has a significant impact on the organizational culture of employees at RSUD Kotabumi Lampung Utara, transformational leadership has a significant impact on the public service motivation of employees at RSUD Kotabumi Lampung Utara, organizational culture does not have a significant impact on the performance of employees at RSUD Kotabumi Lampung Utara, public service motivation does not have a significant impact on the performance of employees at RSUD Kotabumi Lampung Utara, organizational culture does not mediate the impact of transformational leadership on the performance of employees at RSUD Kotabumi Lampung Utara, public service motivation does not mediate the impact of transformational leadership on the performance of employees at RSUD Kotabumi Lampung Utara. Suggestions for future research are expected to use the latest variables that are closely related to the conditions of human resources in an increasingly competitive work environment.